Food SMEs Face Increasing Competition in the EU Market: Marketing Management Capability Is a Tool for Becoming a Price Maker. Issue 2 (11th October 2013) - Banterle, Alessandro; Cavaliere, Alessia; Carraresi, Laura; Stranieri, Stefanella
ABSTRACT The price‐making ability of food small and medium‐sized enterprises (SME) is important for their market survival. Since pricing is a part of marketing activities, by developing specific marketing capabilities, firms can improve their ability to make pricing decisions. This paper aims at evaluating the relationship between marketing capabilities and a firm's price‐making ability. A survey was conducted based on a sample of 371 food SMEs in the EU. We applied an Ordinal Regression Model to evaluate the determinants of a firm's price‐making ability. The analysis results revealed a certain ability of SMEs to set prices. Market analysis and marketing strategy planning capabilities are positively related to the price‐making ability of a firm, while firm size is not. Supply chain relationships play a crucial role in price‐making due to the strong constraint presented by the presence of vertical competition between food SMEs and supermarkets. (L25, L66, M31)